An original closed reduction technique for acute shoulder dislocation: the wrist-clamping and shoulder-lifting - Wanwu Dai; Lei Liu; Shuang Zong; Yong Zhou; Jun Zheng; Xingyan Li (International Journal of Emergency Medicine)
Abstract Background Acute anterior shoulder dislocation is one of the most common injuries in emergency medicine and orthopaedics. The aim of this study is to introduce a new closed reduction technique: the wrist-clamping and shoulder-lifting, for manual reduction of acute anterior shoulder dislocation. Patients and methods The patient is instructed to a sitting position, the doctor hold the wrist of the arm with both hands, slowly rotated the arm to 90-degree of abduction and 60-degree of external rotation with gentle strength. After the shoulder muscles were relaxed by continuous traction, the wrist of the arm was clamped with knee joints when the arm was in 45-degree of abduction and 60-degree of external rotation. Then place hands on axilla and lift shoulder upward until the reduction is complete. Results Thirty-six dislocated shoulders were successfully reduced with this technique, without fracture and iatrogenic neurovascular complications. No sedation, anesthesia, or intra-articular injection were used in all patients. All reduction procedures were performed by a single operator without assistance, and meantime for reduction was 3 min (range 1–8 min). Conclusions The wrist-clamping and shoulder-lifting technique is a safe, simple, effective, gentle, fast and single-operator for anterior shoulder dislocations. Without sedation, anaesthesia, or intra-articular injection. This closed reduction technique enables orthopedists and emergency physicians to reduce the anterior shoulder dislocation smoothly and quickly, and provide a reliable and alternative reduction technique.